Tri Kaya Parisudha Based Time Token Learning Model Influences Students’ Speaking Skills - Dewi, Ni Luh Pradita; Ganing, Ni Nyoman (Jurnal Ilmiah Sekolah Dasar, 2020)
The problem that underlied in this research was that the students speaking skills were not optimal, the learning model used was less varied, the learning atmosphere in the classroom was less arousing the activeness of students to participate. This study aimed to analyze the influence of Tri Kaya Parisudha based Time Token learning model on the fourth-grade speaking skills of elementary school. The study was a quasi-experimental with Posttest-only No-Treatment Control Group Design. The population of the study was all grade IV elementary schools, namely 16 classes and 495 total of students. The research sample was determined by using cluster random sampling. In this study, the samples were obtained 66 students. Speaking skills data were obtained using structured observation. The obtained data were analyzed using polled variance t-test. Based on data analysis, obtained tcount = 7.042 and ttable (significant level 5%) = 2,000 with dk = 64, then H0 was rejected. So, it is concluded that there was a significant influence of Tri Kaya Parisudha based Time Token learning model on the speaking skill of the fourth grade elementary school. This model can be used as a reference by the teacher in the learning process to improve speaking skills.